AUA Policy Statement on the Use of Multiparametric Magnetic Resonance Imaging in the Diagnosis, Staging and Management of Prostate Cancer - Fulgham, Pat F; Rukstalis, Daniel B; Turkbey, Ismail Baris; Rubenstein, Jonathan N; Taneja, Samir; Carroll, Peter R; Pinto, Peter A; Bjurlin, Marc A; Eggener, Scott (The Journal of urology, 2017)
We summarize the available data about the clinical and economic effectiveness of magnetic resonance imaging in the diagnosis and management of prostate cancer, and provide practical recommendations for its use in the screening, diagnosis, staging and surveillance of prostate cancer. A panel of clinicians with expertise in the diagnosis and management of prostate cancer evaluated the current published literature on the use and effectiveness of magnetic resonance imaging for this disease. When adequate studies were available for analysis, recommendations were made on the basis of data and when adequate studies were not available, recommendations were made on the basis of expert consensus. At this time the data support the use of magnetic resonance imaging in patients with a previous negative biopsy and ongoing concerns about increased risk of prostate cancer. The data regarding its usefulness for initial biopsy suggest a possible role for magnetic resonance imaging in some circumstances. There is currently insufficient evidence to recommend magnetic resonance imaging for screening, staging or surveillance of prostate cancer. Although it adds cost to the management of prostate cancer, magnetic resonance imaging offers superior anatomic detail, and the ability to evaluate cellular density based on water diffusion and blood flow based on contrast enhancement. Imaging targeted biopsy may increase the diagnosis of clinically significant cancers by identifying specific lesions not visible on conventional ultrasound. The clinical indications for the use of magnetic resonance imaging in the management of prostate cancer are rapidly evolving.